A risk assessment of pathogenic Streptococcus suis in pork supply chains and markets in Thailand - Phrutsamon Wongnak (2020)
© 2020 Elsevier Ltd Annually, hundreds of severe foodborne cases related to Streptococcus suis (S. suis) have been reported in Southeast Asia, including Thailand. This study aimed at quantitatively evaluating the S. suis contaminations in pork and surrounding environment in pork production chains and its contributions to human illnesses. Pig-associated and environmental samples were collected from four pork supply chains in Bangkok, and cross-sectional pork samples were collected from traditional market and supermarkets in eight provinces in Thailand. All samples were enumerated for S. suis serotype 2 using standard plate count method, and bacterial species were confirmed by biochemical tests together with PCR assays and Quellung method. A quantitative microbial risk assessment (QMRA) was performed to evaluate the S. suis serotype 2 illness risk from consuming pork in Thailand. Among four pork supply chains, the mean S. suis prevalence of pig-associated, and environmental samples were 10.9% (54/496), and 5.21% (25/480), respectively. S. suis has the highest prevalence (56.3%) (9/16), and the highest concentration (5.6 log CFU/g) in palatine tonsils. S. suis was isolated from 0.93% (11/1180) of pork samples; none of them was serotype 2. The QMRA model revealed a mean daily probability of S. suis serotype 2 illness as 2.32 × 10−8, corresponding to 502 and 31 annual cases and deaths, respectively. Additionally, the illness risk from consuming raw pork was predicted at 5.47 × 10−6. In conclusion, even the probability of S. suis illnesses from consuming pork was considerably low; however, the illnesses could lead to serious health consequences among susceptible populations.